Transmission of potato spindle tuber viroid between Phytophthora infestans and host plants - O. S. Afanasenko; A. V. Khiutti; N. V. Mironenko; N. M. Lashina (Вавиловский журнал генетики и селекции)
Potato spindle tuber viroid (PSTVd) is a naked, circular, single-stranded RNA (356–363 nucleotides in length) which lacks any protein-coding sequences. It is an economically important pathogen and is classified as a high-risk plant quarantine disease. Moreover, it is known that PSTVd is mechanically transmitted by vegetative plant propagation through infected pollen, and by aphids. The aim of this study is to determine the possibility of viroid transmission by potato pathogen Phytophthora infestans (Mont.) de Bary. PSTVd-infected (strain VP87) potato cultivars Gala, Colomba, and Riviera were inoculated with P. infestans isolate PiVZR18, and in 7 days, after the appearance of symptoms, re-isolation of P. infestans on rye agar was conducted. RT-PCR diagnostics of PSTVd in a mixture of mycelia and sporangia were positive after 14 days of cultivation on rye agar. The PSTVd-infected P. infestans isolate PiVZR18v+ was used to inoculate the healthy, viroid-free plants of potato cv. Gala and tomato cv. Zagadka. After 60 days, an amplification fragment of PSTVd was detected in the tissues of one plant of tomato cv. Zagadka by RT-PCR with the primer set P3/P4, indicating successful transmission of PSTVd by P. infestans isolate PiVZR18v+. This result was confirmed by sequencing of the RT-PCR amplicon with primers P3/P4. The partial sequence of this amplicon was identical (99.5 %) to PSTVd strain VP87. RT-PCR showed the possibility of viroid stability in a pure culture of P. infestans isolate PiVZR18v+ after three consecutive passages on rye agar. PSTVd was not detected after the eighth passage on rye agar in P. infestans subculture. These results are initial evidence of potato viroid PSTVd being bidirectionally transferred between P. infestans and host plants.